Solving Quadratic Problems Involving Brackets

Algebra: Solve for x Help

Home | Solve for x menu | Algebra menu

Suppose you have a problem like:

(2x-5)(3x-2) = (-4x-3)(x+2)

All you do is use FOIL to get rid of the brackets. In our example we get:

(2x-5)(3x-2) = (-4x-3)(x+2)

6x2-19x+10 = -4x2-11x-6

We can then proceed with our basic strategy.

AN EXCEPTION TO USING FOIL. Check to see if there is a common term on either side of the equation. If there is, you can divide by that term (the caveat is that it is not equal to zero).


(2x-5)(3x-2) = (-4x-3)(3x-2)

Assuming that x = 2/3 is not a solution, we can divide both sides of the equation by (3x-2).

(2x-5)(3x-2) = (-4x-3)(3x-2)

2x-5 = -4x-3

This makes your life a bit easier.

privacy policy